1998
DOI: 10.1097/00005537-199803000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin on Tinnitus

Abstract: Melatonin has been shown to be useful in the treatment of subjective tinnitus. Patients with high THI scores and/or difficulty sleeping are most likely to benefit from treatment with melatonin. In light of its minimal side effects, melatonin should be a part of the physician's armamentarium in the treatment of tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
4
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 8 publications
2
50
4
3
Order By: Relevance
“…83 Some researchers have suggested that increasing intake of various dietary components, particularly vitamin B, zinc, and magnesium, could help tinnitus. Existing evidence is of poor quality and contradictory, although magnesium and several other vitamins and minerals are being investigated as potential otoprotectants.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…83 Some researchers have suggested that increasing intake of various dietary components, particularly vitamin B, zinc, and magnesium, could help tinnitus. Existing evidence is of poor quality and contradictory, although magnesium and several other vitamins and minerals are being investigated as potential otoprotectants.…”
Section: Drug Treatmentsmentioning
confidence: 99%
“…214 Only 1 study reported possible adverse effects of melatonin, which included bad dreams and fatigue. 215 …”
Section: Melatoninmentioning
confidence: 99%
“…Melatonin is the hormone secreted by the pineal gland and connected with cyclic activities. It has been proposed for tinnitus treatment [18] .…”
Section: Tinnitus As a Circadian System Disordermentioning
confidence: 99%